Simplicity and complexity in the visual layout of the designs Children magazine covers (Al-Academy, 2018)
The magazine covers the subjects of (simplicity and complexity in the visual layout of the designs of magazine coverings of children) Chapter I The problem and importance of the goal and limits of research and addition to Terminology. In the second chapter the theoretical framework in which the first topic the role of simplicity and complexity in the design and the second section Visual design and design relations and the third research design in magazine covers and the third chapter includes the methodology of research and analysis and the results and conclusions and sources and the most important result of the research is (simplicity and complexity of design, Continuity and vitality and attract the attention of the receiver through the overlap and harmony, repetition, colors, shape, texture and design relationships between elements and foundations).